Concentration and Size Distribution of Particulate Matter in a Broiler House Ambient Air - Amador, Ismael Rodrigues; Pinto, Jurandir Pereira; Solci, Maria Cristina (Orbital: The Electronic Journal of Chemistry, 2016)
Atmospheric particulate matter (PM) is an important constituent of ambient air. The determination of its concentration and size distribution in different environments is essential because of its ability to penetrate deeply into animal and human respiratory tract. In this study, air sampling was performed in a broiler house to estimate the concentration and size distribution of PM emitted along with its activities. Low-vol impactor (< 10 mm), cyclones (< 2.5 e < 1.0 mm), and Sioutas cascade impactor (> 2.5; 1.0 – 2.5; 0.50 – 1.0; 0.25 – 0.50; < 0.25 mm) connected with membrane pumps were used. PM10 showed high concentration (209 - 533 mg m-3). PM2.5 and PM1.0 initially showed relatively low concentration (20.8 and 16.0 mg m-3 respectively) with significantly increasing levels (412.9 and 344.8 mg m-3 respectively) during the samplings. It was also possible to observe the contribution of fine particles. This was evidenced by the high correlation between PM2.5 and PM1.0 and by the profile of particle distribution in the Sioutas sampler. PM concentration levels are considered excessively high, with great potential to affect animal and human health.DOI: http://dx.doi.org/10.17807/orbital.v8i3.847